Pelatihan Psychological First Aid (PFA) pada Siswi Kelas XI (Sebelas) SMA Negeri 3 Sentani (Indonesian Version) - Yulius Mataputun; Agus Zainuri; Ansar CS; Ermelinda Yersin Putri Larung; Ibrahim Ibrahim; Baharuddin Hasan (Lembaga Pengembangan Kinerja Dosen, 2025)
Students at the High School level often face various emotional and psychological challenges, such as academic stress, social pressure, and personal crises, which can negatively affect their mental well-being. To overcome this issue, community service aims to implement Psychological First Aid (PFA) training which provides students with understanding and skills in providing psychological support to colleagues. The focus of this service is to increase awareness of the importance of mental health support in the school environment. The method used involves pretest questionnaires, theory sessions, role plays, group discussions to help students master the basic principles of PFA through real situation simulations and ends with a post test. The results of PKM activities are (1) most participants gained an increased understanding of Psychological First Aid (PFA); (2) Most participants easily practiced Psychological First Aid (PFA) with their friends during role play sessions. The conclusions from this service are (1) increasing the knowledge and skills of female students at SMA Negeri 3 Sentani in applying Psychological First Aid (PFA) to their peers; (2) Collaboration between FIK UNCEN and SMA Negeri 3 Sentani; (3) carrying out community service activities as a lecturer's academic obligation.